DNA Replication Methods and Protocols - Vengrova, Sonya; Dalgaard, Jacob; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
Updated and revised, this thorough volume covers a range of methods focusing on systems, including mammalian, yeast, bacterial and archaeal. This second edition of DNA Replication: Methods and Protocols describes approaches to analyze whole genomes to single molecules, as well as both in vivo and in vitro experiments.  As a volume in the highly successful Methods in Molecular Biology series, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, DNA Replication: Methods and Protocols, Second Edition provides a collections of methods intended for newcomers to this research field and for established laboratories.
A High-Throughput Confocal Fluorescence Microscopy Platform to Study DNA Replication Stress in Yeast Cells -- Microscopy Techniques to Examine DNA Replication in Fission Yeast -- High-Resolution Analysis of Mammalian DNA Replication Units -- Analysing the Dynamics of DNA Replication In Mammalian Cells Using DNA Combing -- Measuring DNA Content by Flow Cytometry in Fission Yeast -- Incorporation of Thymidine Analogs for Studying Replication Kinetics In Fission Yeast -- Edu Incorporation for FACS and Microscopy Analysis of DNA Replication in Budding Yeast -- Determination Of Deoxyribonucleoside Triphosphate Concentrations in Yeast Cells by Strong Anion-Exchange High-Performance Liquid Chromatography Coupled with Ultraviolet Detection -- Measuring Ribonucleotide Incorporation Into DNA In Vitro and In Vivo -- Detection And Sequencing Of Okazaki Fragments In S. Cerevisiae -- Chip-Seq To Analyze The Binding Of Replication Proteins To Chromatin -- Chromatin Immunoprecipitation To Detect DNA Replication And Repair Factors -- Molecular Genetic Methods To Study DNA Replication Protein Function In Haloferax Volcanii, A Model Archaeal Organism -- Single-Molecule Observation Of Prokaryotic DNA Replication -- Analysing the Response to Dysfunction Replication Forks Using the RTS1 Barrier System in Fission Yeast -- Purification of Restriction Fragments Containing Replication Intermediates from Complex Genomes for 2-D Gel Analysis -- Isolation of Restriction Fragments Containing Origins of Replication from Complex Genomes.
Keywords: Medical genetics; Gene Function